2011 Electrical Insulation Conference (EIC). 2011
DOI: 10.1109/eic.2011.5996182
|View full text |Cite
|
Sign up to set email alerts
|

Electric field computation of water droplets on a model insulator

Abstract: The effect of droplets on the surface of the overhead insulators (porcelain and silicone rubber) and their contributions to electric field distribution and hence possibility of failure is investigated. Initially the variation of electric field distribution around a typical water droplet in the sheath and shed regions as a function of contact angle is investigated. The effect on field distribution in presence of multiple droplets is explored by varying the number, the relative positioning and contact angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Possible effects of an electric field on ice nucleation range from nanoscale effects involving the orientation of the dipole water molecules (Yan et al, 2014) to macroscale phenomena, such as droplet oscillation in the case of an alternating electric field (Reguera and Rubí, 2003;Löwe et al, 2020;Schütte and Hornfeldt, 1990). Since ice nucleation is a physical process which is extremely sensitive to a variety of parameters, the experimental boundary conditions must be precisely controlled in order to distinguish unambiguously the effects on ice nucleation.…”
Section: Discussion Of the Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible effects of an electric field on ice nucleation range from nanoscale effects involving the orientation of the dipole water molecules (Yan et al, 2014) to macroscale phenomena, such as droplet oscillation in the case of an alternating electric field (Reguera and Rubí, 2003;Löwe et al, 2020;Schütte and Hornfeldt, 1990). Since ice nucleation is a physical process which is extremely sensitive to a variety of parameters, the experimental boundary conditions must be precisely controlled in order to distinguish unambiguously the effects on ice nucleation.…”
Section: Discussion Of the Boundary Conditionsmentioning
confidence: 99%
“…Not only the amplitude and frequency but also the oscillation mode of a sessile droplet may significantly vary for varying boundary conditions, e.g., electric field strength, charge, or droplet size (Löwe et al, 2020). Depending on these parameters, various oscillation modes ranging from droplet oscillation mainly parallel to the surface to oscillations perpendicular to the surface or mixed oscillation modes are possible (Löwe et al, 2020;Schütte and Hornfeldt, 1990). Each of these modes is associated with a different interaction between the moving fluid molecules and the substrate where ice nucleation is predominantly expected.…”
Section: Droplet Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…This orientation and the resulting tangentially aligned electric field is chosen to account for the associated macroscopic droplet behavior. In terms of droplet deformation and excitation, a tangentially aligned electric field has a significantly stronger effect on a sessile droplet compared to an electric field aligned normal to the surface (Sarang et al (2011)) and it represents the typical situation on a line insulator. Accordingly, also the effect of the electric field on nucleation is expected to be higher in the case of a tangentially aligned field.…”
Section: Electric Field Generationmentioning
confidence: 99%
“…silicon rubber and porcelain) against the electric field has been researched. The result showed that E-field intensity depended on the distance between the water droplets and the electrodes and also on the relative distance between two water droplets and for multiple droplets the field patterns varied with respect to the change in number, relative position, contact angle of droplets and the location of the water droplet is more significant compared with the number of water droplets [7]. Meanwhile, these water droplets cause the electric field enhancements at the triple points (interfacial point of three dielectric mediums i.e.…”
Section: Introductionmentioning
confidence: 99%